2006
DOI: 10.1007/bf03167971
|View full text |Cite
|
Sign up to set email alerts
|

Management of spontaneous rupture of the oesophagus (Boerhaave’s syndrome): Single centre experience of 18 cases

Abstract: Surgical intervention remains the gold standard when the diagnosis is made early. For late diagnoses, this series suggests caution in the use of endoprostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Most case series of esophageal perforation come from central teaching hospitals, only a few of which are from the UK 1,12–14 . Therefore, our aim was to perform a 13‐year retrospective review of the cases managed in our peripheral district general hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most case series of esophageal perforation come from central teaching hospitals, only a few of which are from the UK 1,12–14 . Therefore, our aim was to perform a 13‐year retrospective review of the cases managed in our peripheral district general hospital.…”
Section: Introductionmentioning
confidence: 99%
“…11 Most case series of esophageal perforation come from central teaching hospitals, only a few of which are from the UK. 1,[12][13][14] Therefore, our aim was to perform a 13-year retrospective review of the cases managed in our peripheral district general hospital. Our purpose was to learn more about the management of esophageal perforation in the era of improved diagnostic imaging and access to a wide variety of potential surgical and nonsurgical treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Some advocate primary surgical repair as the gold standard treatment in all patients able to tolerate surgery, with best outcomes when performed within 24 h 3 17. Some studies, however, suggest surgery beyond 24 h may still improve outcome and reduce mortality 18–20.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative leakage happened in four cases and two died of uncontrolled sepsis, but only one died after primary repair. The fact gives us reason to propose: regardless of the time delay, transthoracic primary repair should be the first choice for treating BS patients; other techniques, such as drainage alone, exclusion and diversion, or esophageal resection may be appropriate in certain circumstances 6,10,14,48–50 …”
Section: Discussionmentioning
confidence: 99%
“…The fact gives us reason to propose: regardless of the time delay, transthoracic primary repair should be the first choice for treating BS patients; other techniques, such as drainage alone, exclusion and diversion, or esophageal resection may be appropriate in certain circumstances. 6,10,14,[48][49][50] Although, some reported that selected esophageal laceration might not need repair if only the pleural effusion had been drained thoroughly and the infection had been controlled completely. 10,49,51,52 Our experience showed that esophageal tear is hard to heal spontaneously as the infection is hard to control when negative intrathoracic pressure and mechanical movement of the chest during ventilation ensures dissipation of these toxic substances within the mediastinum and pleura.…”
Section: Discussionmentioning
confidence: 99%